The problem of humanism in Kazakh philosophy - Balabekova, L.G. (Karagandy University of the name of acad. E.A. Buketov, 2025)
In this article, the problem of humanism in Kazakh philosophy is considered in detail from a theoretical and historical point of view. In the course of the study, based on the works of foreign (M. Scheler, T. Parsons, R. Inglhart, E. Durkheim, K. Klakhon) and domestic (Abai Kunanbaiuly, Shakarim Kudaiberdiuly, A. Baitursynuly, M. Dulatov, M. Auezov, S. Toraigyrov) thinkers, the essence of humanistic values, their place in the philosophical system and modern forms of expression were analyzed. The article reveals the historical basis and continuity of such humanistic principles as morality, conscience, inner freedom, charity in the traditional worldview of the Kazakh people. At the same time, in the context of modern globalization, urbanization and value transformation, the relevance of the ideas of humanism and the need for their reproduction in society are substantiated. As a result of the study, the place of humanism in the Kazakh philosophical thought, its importance in the spiritual development of the individual, as well as its role in the modernization of national consciousness were scientifically proved. The article contributes to the humanistic search within the framework of Kazakh philosophy and provides relevance for today’s social and humanitarian sciences. Humanism in Kazakh philosophy is not just a system of ideas remaining in the historical consciousness, but a set of life orientations that guide modern society. Humanistic views in the works of Kazakh thinkers reflect the path of human and spiritual improvement. Therefore, in modern socio-cultural conditions, the revival of humanistic thought in national philosophy is of strategic importance for the spiritual development of our country.
Keywords: the doctrine of conscience; Shakarim; Abai; traditions; personality; spiritual culture; value system; humanism; Kazakh philosophy